Analysis Of Financial Performance Of Muhammadiyah Aisyiyah Hospital In Jakarta Before And After The Covid-19 Pandemic - Pantjatmono, Teguh; Priharta, Andry; Riyanti, Riyanti (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
This study aims to analyze differences in the financial performance of the Muhammadiyah-Aisyiyah Hospital (RSMA) in Jakarta before and after the COVID-19 pandemic. Data was obtained from financial reports (2017Q1-2022Q4) which were analyzed using the ANOVA difference test. Based on the analysis and discussion, it was found that there was a significant difference in financial performance in the financial ratios of TATO and PBT, while the difference in DAR was not significant before and after the COVID-19 pandemic in the RSIJ Group. Apart from that, it was found that financial performance was better after the COVID-19 pandemic.This research provides practical insights for hospital managers and stakeholders in designing more effective policies for financial management during and after the pandemic. The increase in the Debt to Assets Ratio in several hospitals shows the need for better debt management strategies, while the decrease in the Total Assets Turnover Ratio emphasizes the importance of increasing the efficiency of assets use. The increase in Profit Before Tax in several hospitals indicates opportunities to increase profitability through appropriate management despite existing challenges. To improve the financial performance of Muhammadiyah private hospitals in DKI Jakarta, it is recommended to improve asset management to make it more effective, diversify income sources to reduce financial risks, improve revenue and operational expense management strategies, and invest in advanced health technology.